Performance Assessment of Fuzzy Logic Power System Stabilizer on North Benghazi Power Plant. (30th May 2013) - Hussein, T.; Shamekh, A.
Abstract : Fuzzy logic design has been implemented online to tune the power system stabilizer gain (K PSS ). To assess the performance of the proposed technique, Benghazi North Power Plant (BNPP), at eastern Libyan network, has been utilized as a power system stabilizer (PSS) benchmark. The design considers different operating conditions and large disturbance. A selection of fuzzy rules is derived by means of system output power to tuneK PSS, whereas Particle Swarm Optimization technique (PSO) is exploited to calculate the PSS parameters offline according to real-time measurements of the considered plant. Several simulation scenarios have been conducted to show the effectiveness of the proposed PSS in damping of local and interarea modes of oscillation of one-machine infinite-bus system. The study also contains comparison between the proposed technique and conventional PSS (CPSS).